THE IMPLEMENTATION OF FUN FISHING TO TEACH SPEAKING FOR ELEMENTARY SCHOOL STUDENTS - Robekka Risten Fransiska Sinaga; Lulud Oktaviani (Journal of English Language Teaching and Learning, 2020)
To produce competitive students that ready to face the trend of language learning in English as a foreign language, especially speaking skills, teachers should be ready to develop good planning in the teaching process. It can be in the form of strategies that can motivate students in the learning process. Moreover, in teaching elementary school students, teachers should be more creative to encourage students’ motivation in speaking by using attractive teaching media which involves physical activity because young learners usually only have a short attention span. By using teaching media, students will learn a language in such attractive and fun ways. Thus, the researchers want to see the use of Fun Fishing in teaching speaking at one of the Elementary Schools in Lampung to encourage students in learning English. This research used a qualitative method since it disclosed how to implement Fun Fishing media in an Elementary School in Lampung. As a result, the students were divided into four groups consisted of 2-3 members and learned English which involved physical activity. To sum up, using this media in learning English can motivate students to speak in English and make teaching and learning become more fun because they did physical activity.